Hydrological processes (water use and balance) in a coffee (Coffea arabica L.) monoculture and a coffee plantation shaded by Inga densiflora in Costa Rica - Siles Gutiérrez, P. (Université Henri Poincaré, Nancy (Francia) CIRAD, Montpellier (Francia) CATIE, Turrialba (Costa Rica) Institut National de la Recherche Agronomique, París (Francia), 2014)
Ilus. Tab. Bib.